2001
DOI: 10.1183/09031936.01.00053501
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory flow limitation during sleep in pre-eclampsia: comparison with normal pregnant and nonpregnant women

Abstract: Self-reported snoring is common in pregnancy, particularly in females with pre-eclampsia. The prevalence of inspiratory flow limitation during sleep in pre-eclamptic females was objectively assessed and compared with normal pregnant and nonpregnant females.Fifteen females with pre-eclampsia were compared to 15 females from each of the three trimesters of pregnancy, as well as to 15 matched nonpregnant control females (total study population, 75 subjects). All subjects had overnight monitoring of respiration, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 24 publications
6
57
0
1
Order By: Relevance
“…Differences in risk factors between women with mild and severe pre-eclampsia include higher maternal weight and a higher predilection for metabolic syndrome in those with the milder pre-eclampsia phenotype. (32) As it relates to SDB, mild pre-eclampsia may be a marker for women at risk for snoring or SDB when confronted with pregnancy-related weight gain or fluid changes; (33)(34)(35)(36)(37) or the association we observed may relate to an underlying genetic predisposition of both mothers and their children to upper airway obstruction or to obesity-related diseases. (38) Differences in the association of SDB with mild as compared to severe pre-eclampsia may also be due to differences in smoking exposures in each group and potential confounding by this exposure.…”
Section: Discussionmentioning
confidence: 91%
“…Differences in risk factors between women with mild and severe pre-eclampsia include higher maternal weight and a higher predilection for metabolic syndrome in those with the milder pre-eclampsia phenotype. (32) As it relates to SDB, mild pre-eclampsia may be a marker for women at risk for snoring or SDB when confronted with pregnancy-related weight gain or fluid changes; (33)(34)(35)(36)(37) or the association we observed may relate to an underlying genetic predisposition of both mothers and their children to upper airway obstruction or to obesity-related diseases. (38) Differences in the association of SDB with mild as compared to severe pre-eclampsia may also be due to differences in smoking exposures in each group and potential confounding by this exposure.…”
Section: Discussionmentioning
confidence: 91%
“…There are several studies on SDB in pregnancy, but most are based on questionnaires [1,2] or clinical examinations [12] or focused on pre-eclampsia [3,4,23]. Therefore, this study would seem to be one of the first that presents both objective and subjective measurements regarding SDB in healthy pregnant females.…”
Section: Discussionmentioning
confidence: 99%
“…CONNOLLY et al [29] reported increased periods of inspiratory flow limitation among 15 pre-eclamptic females compared with normotensive pregnant females, although the AHI based on the o50% reduction in airflow did not differ between study groups. EDWARDS et al [30] reported similar findings, although the flow limitation episodes were not quantified.…”
Section: Controls N=33mentioning
confidence: 99%